Evaluation of Several Hematologic and Serological Parameters in Rheumatoid Arthritis Patients - Jabbar Diwan, Zahraa; Addai Al- Marsomy, Wasan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Rheumatoid arthritis (RA) is a chronic inflammatory disease that primarily affects the synovial joints and produces recurring inflammation of the synovial membrane, which ultimately causes joint degeneration, deformity, and disability. The current study included 110 blood samples collected from patients infected with rheumatoid arthritis (60) and 50 blood samples from controls. The results showed that investigation of some hematological tests revealed a high significant erythrocyte sedimentation rate (ESR) for the patient group compared to the control group (28.25 ± 2.72, 16.24 ± 1.83), respectively. But it is non-significant for patients for (WBC, RBC, and PLT) was (7.34 ± 0.25, 4.71 ± 0.08, and 248.26 ± 9.18), while the control group was (6.73 ±0.19, 4.96 ±0.10, and 263.64 ±8.26), respectively. As well as the result of the rheumatoid arthritis factor (Rh) level, there was a significant increase in patients with positive RF 45 (75.00%) and negative RF 15 (25.00%). while the result for the C-reactive protein (CRP) test for patients was positive 26 (43.33%) and negative 34 (56.67%).